Reevaluating Qur'anic Hermeneutics: A Comparative Analysis Between Classical Tafsir and Modern Hermeneutical Approaches - Ichwan, Moh. Nor; Salisu, Auwal (KALAM, 2024)
This study discusses the methodological differences between classical interpretation and modern hermeneutic approaches in interpreting the Qur'an. Classical interpretation, represented by works such as Tafsir al-Tabari and Tafsir Ibn Kathir, tends to emphasize the authority of tradition and the literal understanding of the Qur'anic text. In contrast, modern hermeneutics, developed by scholars such as Fazlur Rahman and Nasr Hamid Abu Zayd, offers a more contextual and critical approach to texts, considering historical and social factors. This study aims to explore the strengths and weaknesses of the two approaches and assess the potential for combining the two elements. Using comparative methods and thematic analysis, this study finds that classical interpretation excels in maintaining the text's integrity but is less flexible in responding to contemporary challenges. On the other hand, modern hermeneutics is more relevant to today's socio-political context, although it faces criticism regarding the legitimacy and authority of the text. This study recommends further study of how ijtihad can bridge the gap between tradition and modernity, creating a more inclusive approach to interpreting the Qur'an.